Non-Destructive Evaluation of Concrete Strength Grades Using Dielectric Permittivity Measurements - Anderson Ngap Chai Kho; Yi Lung Then; Chee Khoon Ng; Dyg Norkhairunnisa Abang Zaidel; Kok Yeow You (International Journal of Integrated Engineering, 2026)
Concrete strength evaluation traditionally relies on destructive compressive testing, which is time-consuming and impractical for continuous monitoring. A review of on-going and current research on non-destructive testing of concrete is presented. This study investigates the use of dielectric permittivity as a non-destructive parameter for distinguishing concrete strength grades. Concrete samples with varying cement–sand–aggregate–water ratios corresponding to C16/20, C20/25, and C25/30 grades were prepared, cured, and measured using an open-ended coaxial dielectric probe connected to a vector network analyzer at ~2.0 GHz. Results show that dielectric permittivity decreases systematically with increasing strength grade, reflecting reduced water content and denser microstructure. Regression analysis demonstrated that exponential models achieved higher accuracy than linear models for concrete grades C20/25 and C25/30. The linear regression model is seen to be more suited for concrete grade C25/30, possibly due to its initial permittivity values are low compared to the other two concrete grades. The coefficient of determination, or R2 values for the linear regression models are 0.4971, 0.5761, and 0.4932, whereas for the exponential regression models are 0.5089, 0.5942, and 0.4757 respectively for the three concrete grades C16/20, C20/25, and C25/30. The research concludes that the experimental work demonstrated the measured real part of the complex permittivity values shows a distinguishable difference between each of the concrete grade. The trend in the values also show that they decrease drastically in the first 5 days, down to almost 50% of their initial measurements. The findings from this research have the potential to be investigated further, with the use of dielectric permittivity as a parameter to establish a microwave-based sensing system for monitoring of concrete samples or structures.